He iwi moke, he whanokē : iwi social services, policy and practice : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey University, Manawatū, New Zealand - Rickard, Taimania (Massey University, 2014)
Whanau centred organisational policy and social work practice is well established within iwi and Maori organisations. Shifts in government policy thinking toward more holistic and collaborative social service provision, characterised by the development of Whanau Ora, affirms the past and current practice of iwi and Maori organisations. Te Runanga o Ngati Porou has successfully provided whanau centred social services with the support of government contract funding since 1992. This thesis examines the current policy and practice of the Runanga with reference to the development of Maori social policy and in particular Whanau Ora, arguing that Maori social work practice has developed ahead of and in parallel to official government policy. Emerging themes include Whanau Ora as an established approach within Ngati Porou and the Maori social service sector, the impact of politics and the economy on direction and service provision, community influenced social work, the natural and forced inclusion of tikanga in social services and research and the potential for official whanau centred social policy to increase the effectiveness of iwi and Maori organisations to deliver services in line with a Maori world view. This study was completed within a Kaupapa Maori research framework specifically tailored for the project. Recommendations for future research, both specific to the Ngati Porou community and to Maori development in general are made at the conclusion of the thesis. Recommendations for iwi social service providers and the public sector are also made.
Keywords: Social service; Social policy; New Zealand; Māori; Whānau Ora; Kaupapa Māori; Ngāti Porou; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Social work